Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila di Kelas V Sekolah Dasar - Ridho Rahman; Reinita Reinita (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research is based on field observations which indicate that low student learning outcomes are caused by a lack of active involvement in the learning process, which is still dominated by a teacher-focused learning approach. Therefore, the aim of this research is to explain the increase in student learning outcomes in Pancasila education lessons using the Example Non Example cooperative model in Class V of SDN 11 Marunggi, Kota Pariaman. This research is included in the category of classroom action research (PTK) with a combination of qualitative and quantitative approaches. The research process was carried out in two cycles consisting of planning, implementation, observation and reflection stages. Data was collected relating to learning outcomes implemented through the Example Non Example Cooperative model. Data collection methods include observational, test and non-test analysis. The research subjects consisted of class teachers in the role of observers, researchers in the role of practitioners, and 21 class V students at SDN 11 Marunggi, Pariaman City. The research results show that the teaching module in cycle I reached a percentage of 85.42% (Good), which increased to 95.83% (Very Good) in cycle II. The implementation of learning by teachers in cycle I showed a percentage of 83.33% (Good) and increased to 95.83% (Very Good) in cycle II. Student learning implementation in cycle I also reached a percentage of 83.33% (Good), which increased to 95.83% (Very Good) in cycle II. Student learning outcomes in cycle I recorded an average of 73.65% (Fair), which then increased to 83.92% (Good) in cycle II. With that, it can be concluded that using the Example NonExample cooperative model is effective in improving student learning outcomes in the Pancasila Education subject in Class V SDN 11 Marunggi, Kota Pariaman.